Resizing Symbolically the Holocaust: Picture Books for its approach in Elementary Education - Ruiz-Guerrero, Leonor; Molina-Puche, Sebastián (Clio. History and History Teaching, 2020)
Where the word becomes insufficient, and reality becomes unspeakable, the image and fiction can become the only chink to tell what must be told. That is why picture books are revealed to be suitable for addressing the Holocaust issue with young audiences (Bieber, 2018; Kidd, 2005; Walter y March, 1993). This paper presents the analysis of the defining features of picture books dealing with this topic through the study of a corpus of four examples. It delves into the didactic possibilities of a particular title, Bruno. El niño que aprendió a volar, by Nadia Terranova and Ofra Amit (2012). Results make us conclude that it is possible to create images from lyricism to teach the vilest outrage.